Bone marrow derived mesenchymal stem cell response to the RF magnetron sputter deposited hydroxyapatite coating on AZ91 magnesium alloy; Materials Chemistry and Physics; Vol. 221 - Surmeneva M. A. Maria Alexandrovna; Ivanova A. A. Anna Aleksandrovna; Tian Q. Qiaomu; Pittman R. Rebekah; Jiang W. Wensen; Lin J. Jiajia; Liu Huinan H.; Surmenev R. A. Roman Anatolievich (2018, 2018)
Title screen